DOXING AS A DIGITAL CRIME: A HUMAN RIGHTS AND PRIVACY PROTECTION PERSPECTIVE UNDER INDONESIAN LAW - Utami, Sal Sabila Khoirotunnisa (Domus Legalis Cogitatio, 2025)
This article examines doxing as a form of digital crime that infringes on privacy and human rights, with a focus on the legal protections provided by Indonesian law. The study begins by defining the key human rights concepts of freedom of expression and the right to privacy, grounded in international instruments such as the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). This theoretical foundation allows for an in-depth analysis of Indonesian legislation, specifically the Electronic Information and Transactions (ITE) Law and the Personal Data Protection Law (PDP), in addressing the issue of doxing. The research identifies significant legal gaps, particularly the lack of clear definitions and specific provisions targeting doxing, and compares Indonesia’s legal framework with international human rights standards. Through a review of notable doxing cases in Indonesia, the article demonstrates the shortcomings of current legal protections and highlights challenges in prosecuting offenders. A comparative analysis with international doxing laws, including those of the United States, European Union, and South Korea, provides a broader understanding of how various legal systems approach this crime. The article concludes with a central research question: To what extent does Indonesian law address doxing in accordance with international human rights and privacy standards? The study argues that Indonesian law needs clearer definitions, stronger legal provisions, and better alignment with international human rights standards to effectively combat this growing digital threat. Finally, the paper proposes legal reforms to strengthen protections for individuals affected by doxing in the digital age.